MATHEMATICAL ANALYSIS OF ENTERPRISE RISKS - Мормуль, Микола; Щитов, Дмитро; Щитов, Олександр; Романчук, Любов; Чупілко, Тетяна (SWorldJournal, 2023)
Nowadays in the country and world, there is an extremely unstable economic situation with a high measure of vagueness through martial law and battle operating on the territory of Ukraine. Such a situation can gravely threaten its safety, that is why the r